PENGGUNAAN MEDIA SANK MAGIC BOOK UNTUK MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA KELAS II SDN 06/VI PAMENANG KABUPATEN MERANGIN - Hairun Nisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the lack of learning motivation in Mathematics among second-grade students at SD Negeri 06 Pamenang, evidenced by their limited attention, participation, and enthusiasm during lessons. One contributing factor was the use of conventional instructional media, which failed to engage the students. The study aimed to describe the use of the